(untitled) (Research, Society and Development, 2021)
In this study, the Theories of Protection Motivation and Planned Behavior were integrated, in order to determine the factors that affected the intention of preparing among residents of the Administrative Post of Macate, in central Mozambique, to face the tropical cyclone Eloise. Several factors such as perceived severity, perceived vulnerability, perceived behavioral control, subjective norm, attitude and intention to prepare were analyzed using Structural Equation Modeling-SEM. The results showed that the latent variables attitude, perceived vulnerability, perceived behavioral control and subjective norms had a significant direct effect on the preparation intention. The extended model demonstrated a better fit to data preparedness intention to face the effects of the cyclones.